Primary pseudomyogenic hemangioendothelioma of bone: case report and review of the literature - SQUILLACI, S.; PITINO, A.; SPAIRANI, C.; RASSU, P.C.; CHIAPUZZO, E.; KUTZNER, H. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Pseudomyogenic hemangioendothelioma (PMH) represents a multicentric recently characterized tumor type, generally presenting in young adults, of postulated vascular origin and intermediatemalignancy. This entity tends to arise in the deep-seated dermal-subcutaneous locations, preferentially limited to one anatomic site, and may extend secondary to bone. PMH restricted to the skeletal system is rare. To our knowledge, only 19 cases with description of both histologic and clinical findings have been reported to date. We report the clinicopathological features of a further intraosseous PMH occurring in a 46-year-old woman involving the right patella. Histologic examination showed aninfiltrating growth compo ed of sheets and fascicles of spindled to epithelioid large cells, with ample eosinophilic cytoplasm, large vesicular nuclei and prominent nucleoli, sometimes resembling rhabdomyoblastic tumor cells, without morphologic signs of vascular differentiation. At immunohistochemical examination, neoplastic cells stained diffusely for AE1/AE3 keratins, vimentin, ERG, FLI-1, INI-1, FOSB with only focal CD31 expression.The morphologic clues leading to the correct diagnosis of intraosseous PMH havebeen correlated with the data of the literature,and a special emphasis has been given to the differential diagnosis with other neoplasms, particularly epithelioid sarcoma, in order to avoid unnecessary radical surgery and to optimise possible treatment protocols.